Associação entre marcadores inflamatórios e obesidade sarcopênica em idosos em contexto de vulnerabilidade social - Ribeiro, Julio Cesar (Universidade Federal de São Carlos, 2019)
The aging of the world population is the result of environmental factors and technical and scientific advances, which have provided greater longevity. Among the changes resulting from the aging process, changes in body composition are frequently observed. Throughout the aging process, there is a marked progressive loss of muscle mass and strength, called sarcopenia and dynapenia, respectively. We can also mention the physiological changes and body composition that occur during aging, which affect the muscular system, we can include the increase of noncontractile tissue (fat and connective tissue) in the muscle. Therefore, the aim of the present study was to verify whether there are differences in relation to anthropometric, metabolic and inflammatory factors between elderly people with obesity and sarcopenia, alone or together, compared with elderly people who do not have these conditions. A total of 852 older adults registered in the health system database of the Family Health Unit (USF) located in a place of high social vulnerability in the city of São Carlos, São Paulo, Brazil, called “Cidade Aracy”, were registered in a databank. Of these, 342 participants were allocated and divided into four groups, namely: obese, sarcopenic, obese sarcopenic and eutrophic (non-obese) and nonsarcopenic participants. The results indicated several differences in relation to the variables studied between all groups. In highlight, we observed that individuals with sarcopenic obesity were predominantly women, with lower levels of physical activity, higher glycemic levels, glycated hemoglobin, insulin, VLDL cholesterol, triglycerides and growth hormone (GH). These participants also had lower levels of vitamin D and higher levels of the pro-inflammatory cytokine TNF a, compared to the other study groups. The results of this study may help to better characterize the condition of sarcopenic obesity and propose preventive actions for this condition in the older adults who live in conditions of high social vulnerability.
Association between inflammatory markers and sarcopenic obesity in the elderly in context of social vulnerability
Keywords: Envelhecimento; Obesidade sarcopênica; Obesidade; Sarcopênia; Aging; Sarcopenic obesity; Obesity; Sarcopenia; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL